Novel immune‐related signature based on immune cells for predicting prognosis and immunotherapy response in clear cell renal cell carcinoma. Issue 6 (20th April 2022) - Zhou, Libin; Fang, Hualong; Yin, Min; Long, Huimin; Weng, Guobin
Abstract: Background: Clear cell renal cell carcinoma (ccRCC) is the most common malignant tumor of the kidney and is characterized by poor prognosis. We sought to build an immune‐related prognostic signature and investigate its relationship with immunotherapy response in ccRCC. Methods: Immune‐related genes were identified by ssGSEA and WGCNA. The prognostic signature was conducted via univariate, least absolute shrinkage and selection operator, and multivariable Cox regression analyses. Kaplan‐Meier analysis, PCA, t ‐SNE, and ROC were used to evaluate the risk model. Results: A total of 119 immune‐related genes associated with prognosis were screened out. Six immune‐related genes (CSF1, CD5L, AIM2, TIMP3, IRF6, and HHLA2) were applied to construct a prognostic signature for KIRC. Kaplan–Meier analysis showed that patients in high‐risk group had a poorer survival outcome than in low‐risk group. The 1‐, 3‐ and 5‐year AUC of the prognostic signature was 0.754, 0.715, and 0.739, respectively. Univariate and multivariate Cox regression models demonstrated that the risk signature was an independent prognostic factor for KIRC survival. GSEA analysis suggested that the high‐risk group was concentrated on immune‐related pathways. The high‐risk group with more regulatory T‐cell infiltration showed a higher expression of immune negative regulation genes. The risk score had positively relationship with TIDE score and negatively with the response of immunotherapy. The IC50 values of axitinib, sunitinib, sorafenib, and temsirolimus were lower in the high‐risk group. Conclusion: Our study defined a robust signature that may be promising for predicting clinical outcomes and immunotherapy and targeted therapy response in ccRCC patients. Abstract : The risk model for immnotherapy and targted therapy.